Indihome Product Sales Forecasting with the Double Moving Average and Double Exponential Smoothing Methods on PT. Telkom Witel Sumut Pematang Siantar - Deby Natalia L Tobing (Formosa Journal of Science and Technology, 2022)
In this era of globalization, technological developments in Indonesia are growing rapidly, where all activities carried out certainly require information that can be obtained from the internet. In this case the product offered is Indihome. This study uses data on monthly sales of Indihome products by PT. Telkom Witel Sumut Pematang Siantar. The results of this study produced the best parameters and models for each method. The Double Moving Average method with 2 period parameters has a model of ft+p = at + bt P and the Double Exponential Smoothing method with parameters α = 1.0 and β = 0.08 and has a model of ft = St + Tt. The accuracy test of the 2-period Double Moving Average shows a MAPE value of 10% while the Double Exponential Smoothing with α = 1.0 and β = 0.08 shows a MAPE value of 13%. The best forecasting model in forecasting sales of Indihome products PT. Telkom Witel Sumut Pematang Siantar, namely the Double Moving Average method with 2 periods.